Anti-chlamydial activity of vaginal fluids: new evidence from an in vitro model - Morselli, Sara; Ceccarani, Camilla; Djusse, Marielle Ezekielle; Laghi, Luca; Camboni, Tania; Consolandi, Clarissa; Foschi, Claudio; Severgnini, Marco; Marangoni, Antonella (Frontiers in Cellular and Infection Microbiology, 2024)
We assessed the in vitro anti-chlamydial activity of fresh vaginal secretions, deciphering the microbial and metabolic components able to counteract Chlamydia trachomatis viability. Forty vaginal samples were collected from a group of reproductive-aged women and their anti-chlamydial activity was evaluated by inhibition experiments. Each sample underwent 16S rRNA metabarcoding sequencing to determine the bacterial composition, as well as 1 H-NMR spectroscopy to detect and quantify the presence of vaginal metabolites.Samples characterized by a high anti-chlamydial activity were enriched in Lactobacillus, especially Lactobacillus crispatus and Lactobacillus iners, while not-active samples exhibited a significant reduction of lactobacilli, along with higher relative abundances of Streptococcus and Olegusella.Lactobacillus gasseri showed an opposite behavior compared to L. crispatus, being more prevalent in not-active vaginal samples.Higher concentrations of several amino acids (i.e., isoleucine, leucine, and aspartate; positively correlated to the abundance of L. crispatus and L. jensenii) lactate, and 4-aminobutyrate were the most significant metabolic fingerprints of highly active samples. Acetate and formate concentrations, on the other hand, were related to the abundances of a group of anaerobic opportunistic bacteria (including Prevotella, Dialister, Olegusella, Peptostreptococcus, Peptoniphilus, Finegoldia and Anaerococcus). Finally, glucose, correlated to Streptococcus, Lachnospira and Alloscardovia genera, emerged as a key molecule of the vaginal environment: indeed, the anti-chlamydial effect of vaginal fluids decreased as glucose concentrations increased.These findings could pave the way for novel strategies in the prevention and treatment of chlamydial urogenital infections, such as lactobacilli probiotic formulations or lactobacilli-derived postbiotics.